Analisis Resepsi Viewers Terhadap Tayangan Mistis Sableng TV - Arli Andianto; Santi Delliana (UNIVERSITAS KALBIS, 2022)
The problem in this research is how the audience's acceptance of the mystical Sableng TV shows based on Stuart Hall's theory of meaning, namely Encoding and Decoding. This study aims to find out how the audience interprets the mystical show from Sableng TV episode